Perancangan Sistem Akuntansi Penyusutan Aset Inventaris Politeknik Jambi - Heriyani; Rezagi Meilano; Khuswatun Hasanah; Ernawati Hutabarat (LP2M Politeknik Jambi, 2022)
Politeknik Jambi is the only vocational college in Jambi Province. The process of collecting inventory assets is not optimal when searching for data because there is no calculation of depreciation on inventory assets that are still manual. With that in order to be optimal, it is recommended to use an inventory asset depreciation accounting system. The purpose of this inventory asset depreciation accounting system is to overcome problems that arise in the current system at the Politeknik Jambi and to be a good solution for universities to create a faster and more accurate system in managing inventory assets. Methods of data collection is done by means of interviews, observation, documentation and analysis of the system used by the company.